A Effect of AB Mix Concentration and Variety on the Growth and Yield of Lettuce (Lactuca sativa L.) under a Nutrient Film Technique (NFT) Hydroponic System - Firdaus, Muhammad Hadid; Rusmana , Rusmana; Rohmawati, Imas; Lizansari, Kirana Nugrahayu (Sam Ratulangi University, 2026)
This study evaluated the effect of AB Mix concentration on the growth and yield of lettuce (Lactuca sativa L.) varietiesgrown in a Nutrient Film Technique (NFT) hydroponic system. The experiment was conducted from December 2025 to February 2026 at Allisa Farm, Serang, Banten, Indonesia, using a split-plot design with two factors. The main plotconsisted of AB Mix concentrations at 560, 840, and 1000 ppm, while the subplot included three lettuce varieties: Batavia Caipira, Grand Rapids, and Sementel. Data were analyzed by analysis of variance followed by Duncan’s Multiple RangeTest at the 5% level. AB Mix concentration significantly affected several growth and yield parameters. The 1000 ppm treatment produced the highest number of leaves (19.09), leaf greenness (31.60 SPAD units), root length (21.72 cm), and shoot fresh weight (135.67 g), and supported better plant height during the vegetative stage. Variety also had a significanteffect, with Batavia Caipira showing the best performance in number of leaves, leaf greenness, and shoot fresh weight, while Grand Rapids produced the tallest plants. A significant interaction between AB Mix concentration and variety was observed only for leaf area, with the highest value recorded for 1000 ppm AB Mix combined with Batavia Caipira (94.51 cm²).